Internal short circuit and thermal runaway evolution mechanism of fresh and retired lithium-ion batteries with LiFePO4 cathode during overcharge. (15th December 2022) - Wang, Cong-jie; Zhu, Yan-li; Gao, Fei; Bu, Xin-ya; Chen, Heng-shuai; Quan, Ting; Xu, Yi-bo; Jiao, Qing-jie
Graphical abstract: Highlights: Overcharge-to-thermal-runaway evolution mechanism is analyzed. Joule heat plays a key role in the occurrence of internal short circuit. The effects of various side reactions on thermal runaway are decoupled. The 70% SOH (state of health) battery may be more prone to thermal runaway. Abstract: The safety evolution behavior of LiFePO4 /graphite batteries with different states of health (SOHs) under overcharge is studied based on material morphology, structure, thermal stability and heat analysis. The overcharge results of the 100 % SOH battery show that with increasing state of charge (SOC), the cathode material gradually falls off due to binder oxidation. The number of pores in the separator is significantly reduced when the SOC reaches 120 %, resulting in increased internal resistance. Before the internal short circuit (ISC), the degree of lithium intercalation in the anode increases, and the heat release of the reaction between lithiated graphite and the binder increases, whereas both decrease after ISC due to severe side reactions. The heat release from SEI decomposition increases after ISC as the SOH of the retired battery decreases, while the heat release from the reaction between lithiated graphite and binder decreases. The ISC starts from the positive collector side. Thermal analysis results show that Joule heat plays a key role in the occurrence of ISC. After ISC, Q SEI (SEI decomposition heat) + Q Li - e l e (lithium and electrolyte reaction heat) and Q Li - b i n (lithiated graphite and binder reaction heat) together determine the difference in thermal runaway (TR) behavior of different SOH batteries.